ENVISIONING TOMORROW: THE FUTURE TRAJECTORY OF INDUSTRIAL AUTOMATION - Roberts, Michael (International Journal of Contemporary Research in Marketing and Management Sciences, 2024)
Industrial automation is a cornerstone of modern manufacturing, triggering a substantial shift in industrial productivity. Leveraging seamlessly integrated automation systems, equipment, and production lines, it has delivered heightened production efficiency, reduced production costs, and elevated product quality. The contemporary landscape, marked by the rise of transformative technologies such as the Internet, big data, and cloud computing, block chain, and artificial intelligence, presents a renewed impetus for industrial automation. In response, it is imperative for industrial automation to align with the prevailing trends, advocating the fusion of industrialization and informatization. This strategic fusion is essential to sustain competitiveness amidst the current wave of development.